Tantalum-carbon-integrated nanozymes as a nano-radiosensitizer for radiotherapy enhancement - Li, Rui; Zhao, Weiheng; Wu, Tingting; Wang, Aifeng; Li, Qing; Liu, Ying; Xiong, Huihua (Frontiers in Bioengineering and Biotechnology, 2022)
Radiotherapy (RT) plays a pivotal role in the comprehensive treatment of multiple malignant tumours, exerting its anti-tumour effects through direct induction of double-strand breaks (DSBs) or indirect induction of reactive oxygen species (ROS) production. However, RT resistance remains a therapeutic obstacle that leads to cancer recurrence and treatment failure. In this study, we synthesised a tantalum-carbon-integrated nanozyme with excellent catalase-like (CAT-like) activity and radiosensitivity by immobilising an ultrasmall tantalum nanozyme into an metal-organic framework (MOF)-derived carbon nanozyme through in situ reduction. The integrated tantalum nanozyme significantly increased the CAT activity of the carbon nanozyme, which promoted the production of more oxygen and increased the ROS levels. By improving hypoxia and increasing the level of ROS, more DNA DSBs occur at the cellular level, which, in turn, improves the sensitivity of RT. Moreover, tantalum–carbon-integrated nanozymes combined with RT have demonstrated notable anti-tumour activity in vivo. Therefore, exploiting the enzymatic activity and the effect of ROS amplification of this nanozyme has the potential to overcome resistance to RT, which may offer new horizons for nanozyme-based remedies for biomedical applications.